Human rights, hegemony, and utopia in Latin America: poverty, forced migration and resistance in Mexico and Colombia - Pérez-Bustillo, Camilo (Studies in critical social sciences, 2016)
Human Rights, Hegemony and Utopia in Latin America: Poverty, Forced Migration and Resistance in Mexico and Colombia by Camilo Pérez-Bustillo and Karla Hernández Mares explores the evolving relationship between hegemonic and counter-hegemonic visions of human rights, within the context of cases in contemporary Mexico and Colombia, and their broader implications. The first three chapters provide an introduction to the book´s overall theoretical framework, which will then be applied to a series of more specific issues (migrant rights and the rights of indigenous peoples) and cases (primarily focused on contexts in Mexico and Colombia,), which are intended to be illustrative of broader trends in Latin America and globally.